Construction of Religious Blasphemy Reporting (Framing Analysis of The Case of Muhammad Kece at detik.com and Republika.co.id) - Siti Maisaroh; Lukman Hakim; Citra Owela (UIN Salatiga, 2022)
Blasphemy cases have occurred several times in Indonesia. Recently, a blasphemy case emerged that caused a stir and was criticized by several parties. The case of blasphemy that occurred in 2021 was carried out by a YouTuber named Muhammad Kece. Various reports began to be published by the media. This article discusses the construction of blasphemy reporting by Muhammad Kece on the online media Detik.com and Republika.co.id. This study uses a descriptive qualitative approach by observing the news text. The results show that Detik.com and Republika.co.id is less balanced in reporting this case. However, Detik.com from the beginning did not judge Muhammad Kece as a suspect before there was a decision from the authorities. While Republika.co.id tends to call for the voice of Muslims in its reporting and considers that Muhammad Kece is guilty of blasphemy cases. But in the end the two media agreed that Muhammad Kece was named a suspect and detained.